(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current study was undertaken to explore an innovative approach that employs liquid chromatography (LC) and liquid chromatography-mass spectrometry (LCMS/MS) for the resolution, identification, and characterization of minute quantities of degradation products (DPs) of abemaciclib, without the need for their isolation from reaction mixtures.